Researches related violence against healthcare workers in Turkey: A metaanalysis study - Erbaş, D.H.; Çinar, F.; Aslan, F.E. (Peter Lang AG, 2021)
Objective: This meta-analysis was conducted to systematically review national studies that examine the risk factors, causes, and types of violence in healthcare workers and to evaluate the data obtained through the meta-analysis method. Materials and Methods: Relevant research articles published on the subject between January 2014 and September 2019 were included in the evaluation. Google Scholar, ULAKBIM, Turk Medline, CINAHL, and ClinicalKey database were searched within English, and Turkish "healthcare workers", "healthcare staff", "violence", "hospital" and "Turkey" keywords by making various combinations and 4281 publications were reached in the first stage of the search. Eight studies that met the inclusion criteria were included in the study. Results: The studies included in the study were three descriptive, three crosssectional, one cross-sectional descriptive, and one retrospective observational crosssectional. As a result of the examination aimed at determining the violence against healthcare workers, it was determined that The Violent Incident Form (VIF), white code notification form, and questionnaire form developed by the researchers were used. It was determined that verbal violence occurred in most of the studies, and female employees were at higher risk of being exposed to violence. Conclusion: When the variables that are considered common in all studies are evaluated, it was found that there was no significant difference between the gender and the unit of study and violence, physical violence and being a physician negatively affected the violence. It is thought that this meta-analysis, which was made to determine the risk factors affecting violence in healthcare workers, which is a universal public health problem in the world and in our country, will be a guide for future studies. In this context, the necessity of experimental studies on the subject, as well as determination of risk factors, methods that can be used to prevent violence, and the level of evidence regarding the attitudes of healthcare professionals and patient relatives against violence were put forward. © Peter Lang GmbH. Internationaler Verlag der Wissenschaften Berlin 2021. All rights reserved
Keywords: Healthcare Workers; Hospital; Turkey; Violence